Intelligent Nanomaterials for Solar Energy Harvesting: From Polar Bear Hairs to Unsmooth Nanofiber Fabrication - Wang, Qingli; He, Ji-Huan; Liu, Zhi (Frontiers in Bioengineering and Biotechnology, 2022)
Polar bears can live in an extremely cold environment due to their hairs with some remarkable properties. The hair hollow structure enables the the bear to absorb energy from water, and the white and transparent hairs possess amazing optical property. However, the surface morphology function of bear hair has been little studied. Herein, we demonstrate that the micro structured scales distributed periodically alone the hair can absorb maximal radiative flux from the sun. This polar bear hair-effect has the ability for the hair surface not to reflect radiation with wavelength about 500nm. Mimicking Polar bear’s solar performance in fabrication of nanofibers will certainly stimulate intelligent nanomaterials for efficient solar energy absorbing. Therefore, a new technology is discussed in this work for the fabrication of periodic unsmooth nanofibers towards the solar energy harvesting.